Perancangan Motion Graphic Wisata Edukasi Di Desa Sumbergondo Dengan Teknik Penggabungan Animasi 2d Dan 3d - Sulthon Maulana Rozaq; Evy Poerbaningtyas; Rina Nurfitri (MAVIS : Jurnal Desain Komunikasi Visual, 2022)
Sumbergondo Village is one of the villages in Bumi Aji District, Batu City, East Java, which has a lot of potential, from abundant plantation products to the main potential, namely educational tourism, discussing the recycling of organic and non-organic waste into compost used for plantations. they. Unfortunately, this educational tour is not well-known by tourists, so the need for promotional media packaged in the form of motion graphic videos can explain things that are invisible to the human eye by combining 2-dimensional animation for character animation and typography and 3-dimensional as an asset design in the form of a background packed with a duration of 1 minutes 30 seconds briefly discusses all the potential of Sumbergondo. It can be concluded that if motion graphics and the incorporation of 2-dimensional and 3-dimensional animation are successfully used as promotional media and also make the information in them more conveyed, it is hoped that in the future this educational tour can develop and educate the public in solving waste problems in Indonesia.